The Efficacy of Legal Reforms in Managing Conflict of Interest: Law as a Tool for Handling Conflict of Interest and Corruption - Kwenjera, Peter; Muchangi, IanChris (Strathmore Law Journal, 2022)
Managing conflict of interest in the public sector has been and will always be a concern for governments the world over. This is accentuated for several African countries which continue to rank highly on the corruption and bribery indices. Corruption is closely connected to the issue of conflict of interest and consequently, it is important to seek best practices in place to deal effectively with conflict of interest in the public sector. Various tools and legal instruments have been developed by regional and global organizations with the singular aim of aiding their member states to review and modernise their conflict of interest policies. Some African states have either adopted these instruments as forming part of their municipal law or legislated laws on conflict of interest. This article examines the role played by law in defining and regulating conflict of interest and how conflict of interest affects the public sector in Africa. It focuses on how law can be deployed effectively as a tool of establishing governance structures that maintain a culture that minimizes and manages the occurrence of conflict of interest.